2023
DOI: 10.3390/geriatrics8010019
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular and Epidemiological Investigation of a Large SARS-CoV-2 Outbreak in a Long-Term Care Facility in Luxembourg, 2021

Abstract: In spring 2021, a long-term care facility (LTCF) of 154 residents in Luxembourg experienced a large severe, acute respiratory-syndrome coronavirus 2 (SARS-CoV-2) outbreak a few days after a vaccination campaign. We conducted an outbreak investigation and a serosurvey two months after the outbreak, compared attack rates (AR) among residents and staff, and calculated hospitalization and case-fatality rates (CFR). Whole genome sequencing (WGS) was performed to detect variants in available samples and results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Articles not fulfilling selection criteria and an aggregated dataset containing non-extractable data were excluded from analysis (n=63) (figure 1). 20 Among the 38 included articles, 10 are from the USA, 5 from Italy, 5 from France, 5 from Germany, 3 from Canada, 3 from Spain and Netherlands, and 1 each from the UK, Japan, Serbia, Switzerland and Luxembourg 21–40 44 45 49–64. All studies are observational in nature and mostly, outbreaks were described over a period of 6 months (January–July 2021) (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles not fulfilling selection criteria and an aggregated dataset containing non-extractable data were excluded from analysis (n=63) (figure 1). 20 Among the 38 included articles, 10 are from the USA, 5 from Italy, 5 from France, 5 from Germany, 3 from Canada, 3 from Spain and Netherlands, and 1 each from the UK, Japan, Serbia, Switzerland and Luxembourg 21–40 44 45 49–64. All studies are observational in nature and mostly, outbreaks were described over a period of 6 months (January–July 2021) (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…25 studies reported a pooled hospitalisation rate of 17% (95% CI 13% to 23%, p<0.01) among the confirmed cases of which only 13 articles had information on the vaccination status of hospitalised cases (online supplemental file 1). 21–23 25–27 32 34–39 44 45 49 50 52 54–56 58 60 62 64 The hospitalisation rates were six times lower between vaccinated 4% (95% CI 2% to 7%, p<0.01) and unvaccinated residents 27% (95% CI 12% to 51%, p<0.01) after pooling available data from a total of 13 and 9 studies, respectively (online supplemental file 1). 21 25–27 38 44 58 62 Hospitalisation rates among the vaccinated confirmed cases 14% (95% CI 8% to 23%, p<0.01) declined almost three times lower compared with the unvaccinated confirmed cases 48% (95% CI 32% to 64%, p=0.14) (online supplemental file 1).…”
Section: Resultsmentioning
confidence: 99%